The Role of Human Resources Management in Present Scenario - Mullapudi, Ms. Bhargavi; Sridhar, Dr. P.; Pinakapani, Peri (The journal of contemporary issues in business and government, 2022)
Human Resource Development is the term used to describe the process of developing human resources. Human Resource Management is a philosophy, whereas Human Resource Development refers to the activities and processes that promote the intellectual, moral, psychological, cultural, social, and economic development of individuals in organizations in order to help them reach their full human potential as community resources. It is a constant process in which personnel are aided in developing their abilities in a systematic manner. Human Resources Management is responsible for maximizing efficiency and profit, but in the new environment, the function of HRM is changing Because of developments in government policies, unions, labour laws, and technology, the role of HR managers is fast evolving. Organizational trends, human resource planning, job design, motivation, recruitment, skill development, and employee interactions have all been observed. Human Resource Management may effectively address the difficulties if correct solutions are used. As a result of the changing environment, Human Resources Management will play a larger role in the future. This study aims to explain the current state of human resource management.